1985
DOI: 10.1002/j.1460-2075.1985.tb03887.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and expression of the antigen receptor alpha, beta and gamma genes in suppressor antigen-specific T cell lines.

Abstract: The rearrangement and transcription of the antigen receptor alpha, beta and gamma genes were investigated in murine antigen‐specific suppressor T cell lines, to establish whether the suppressor T cell subset expresses the same antigen receptor transcripts previously found in helper and cytotoxic T lymphocytes. The genomic organization of the alpha, beta and gamma chain loci was investigated using probes representative of the entire gene or fragments from variable, joining and constant regions. The present resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Finally, 7 genes are rearranged in the four cell lines studied but related mRNAs are found only in MP2 and NS8 cells. LH8 cells do not transcribe the 7 gene [24]. Cell surface immunostaining with specific MoAb demonstrated the presence of the jS gene products only on NS8 cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Finally, 7 genes are rearranged in the four cell lines studied but related mRNAs are found only in MP2 and NS8 cells. LH8 cells do not transcribe the 7 gene [24]. Cell surface immunostaining with specific MoAb demonstrated the presence of the jS gene products only on NS8 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Although the NS8 and NS5 cell lines were induced according to the same procedure, they do not show the same restriction pattern. The LH8 and MP2 lines express 1.3 kb 0 RNA transcript ( [24]; this paper), derived from fully assembled V/9, D/3, J0 gene segments and are recognized by MoAb directed against tbe a0-TCR chains. On the opposite, the cytolytic cell line NS8 only presents a partial 0 rearrangement (3/32 is rearranged, C/3 is not) in association with too short /3 chain transcript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the subunit composition ofthe antigen receptor on suppressor T cells (Ts) remains to be solved; several investigators have reported discrepant results, demonstrating that some Ts lines and hybridomas express a-and p-chain genes, whereas some do not (5)(6)(7)(8)(9) despite having their Ts function. Thus, two points should be discussed in this regard.…”
mentioning
confidence: 99%